Restoration of the Production in a Dead Well by using Low Cost Recompletion of Sand Control - Bouba, Apollinaire; Nitcheu, Madeleine; Karga, Lionel Tapsia; Oumate, Alhadji Abba; Nana, Souleymanou Baba; Ngueyep, Luc Leroy Mambou (Control Systems and Optimization Letters, 2023)
This paper proposes a cost-effective solution through a recompletion design of sand control to restart the production of a dead well named "X" (for confidential reasons). The data used to achieve the objective of this paper are the production parameters, reservoir properties and the previous completion design. The tool used to draw the new completion schematic is Power Drawn software. It is necessary to use two softwares (PowerDrawn and Pipesim), Ishikawa method and economic evaluation method. The different causes that probably contributed to the production stop in well X are given by using the Ishikawa diagram. The top sediment is obtained by using the sonic log and the clean-up is performed by using coiled tubing with a drill bit incorporated at the end. The mechanical packer is installed to isolate the formation, the pre-packed screen allows the filtration of hydrocarbons. The on-off tool ensures the installation of the mechanical packer and the minimum restriction for the passage of the equipment through the ones in place is 2.313 inches. After the installation of the recompletion, a positive return on investment is obtained and after a production time of one week. The financial aspect after installation of the recompletion shows that a recompletion of the sand control at lower cost is achieved.